Problems of Teaching Arabic to Non-Native Speakers in Religious Schools in Sri Lanka - Mohamed Nafeel Mohamed Zawahir (UIN Siber Syekh Nurjati Cirebon, Indonesia, 2021)
Sri Lanka is a non-Arab country which gives utmost priority for teachingSinhalese, Tamil and English languages, a question arises on how the teaching activities can be performed according to the academic curricula and regulations, how Arabic language teaching books are composed, and how the religious schools can be supervisedby non-governmental social entities, abiding by the principles of teaching while facing several challenges. This study strives to find the solutions for such issues. To conduct this research, the researcher has followed the descriptive and analytical approach, for which he has taken three long-standing religious colleges namely (Al-Bari Arabic College, Al-Ghafooriya Arabic College and JamiathulFalah Arabic College) that have contributed to boom up the Arabic language in Sri Lanka and have been rendering this service for more than seventy five years. Also the researcher found that teaching methodologies of Arabic language have not been developed enough in Sri Lanka according to the modern era, although it is being taught in various fields and level at national universities, government and religious schools. These institutions follow the traditional curricula in teaching Arabic language. The process of teaching Arabic in Sri Lanka needs to unify the textbooks into a general academic curriculum, which will be suitable for the contemporary world inclusive of all fields of study that are implemented in the religious schools, in addition to appointing Arabic language teachers from Arab countries, planning and implementing projects in order to face the challenges that the Arabic language is going through in Sri Lanka, while encouraging them to teach the functional Arabic language rather than applying traditional memorizing teaching Methods and organizing teacher training.